Emerging drugs for managing kidney disease in patients with diabetes. (March 2013) - Thomas, Merlin C
<x xml:space="preserve">Abstract</x> Introduction: The need for new approaches to manage the increasing numbers of patients with diabetes and their burden of complications is urgent. Of these, chronic kidney disease imposes some of the highest costs, both in dollars and in terms of human suffering. In individuals with diabetes, the presence and severity of kidney disease adversely affects their well-being, contributes to disease morbidity and increases their risk of a premature death. Areas covered: To collect information for the strategies previously or currently under investigation for managing kidney disease in patients with diabetes, a literature search was performed through the search engines PubMed and ClinicalTrials.gov. Expert opinion: Despite advancing knowledge on the pathogenesis of diabetic kidney disease, and promising effects in experimental models, at present there are no new drugs that come close to providing the solutions we desire for our patients. Even when used in combination with standard care, renal complications are at best only modestly reduced, at the considerable expense of additional pill burden and exposure to serious off-target effects. Some of the most exciting advances over the last decade, including thiazolidinediones, direct renin inhibitors, endothelin antagonists and most recently bardoxolone methyl have all fallen at this last hurdle. Better targeted ('smarter') drugs appear to be the best hope for renoprotective therapy.